The association between knowledge and attitude towards nutrition fact panels (NFP) with sugar intake of the Indonesian adolescents - Ulfi Rahma Yunita; Helda Khusun; Fiastuti Witjaksono (World Nutrition Journal, 2024)
The increasing sugar intake has become a global issue due to its impact on health. The survey conducted in Jakarta revealed that the median sugar intake for adolescents and adults is 18.8 g/capital/day and 24.5 g/capital/day, respectively. The government has taken several ways to reduce sugar intake, one of which is by using labels on packaged food. Therefore, this research aims to investigate the knowledge and attitude towards nutrition fact panels with sugar intake in Indonesian adolescent. This research was a cross-sectional study using an online questionnaire for adolescents in Indonesia with age range between 15-18 years old. Data on sociodemographic, mass media exposure, knowledge, and attitude were collected through online questionnaires, while sugar intake was assessed through online SQ-FFQ interviews. The study’s findings showed that the majority of respondents were women (90%), with parents having below 12 years of schooling on average. Additionally, the median monthly pocket money and pocket money for food and drinks below IDR 300,000 and IDR 200,000, and mass media exposure occurred more than 3 times per month. More than half of the respondents displayed good knowledge (51.7%) and a positive attitude towards NFP (60.8%), with the majority having high sugar intake (53.5%). There is a relationship between knowledge of NFP, mass media exposure, and mother education with sugar intake in adolescents. It recommended to enhance knowledge of NFP among adolescents and parents through social media platforms, posters and TV ads to enable them select and consume appropriate foods.